2021
DOI: 10.1002/jsfa.11491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flaxseed cake fortification on bread shelf life, and its possible use as feed for Tenebrio molitor larvae in a circular economy: preliminary results

Abstract: BACKGROUND: Bread represents a significant share of food waste worldwide. The extension of the bread shelf life together with innovative systems of food waste treatment might decrease waste biomass decay, the need for transportation, and the need for storage. In recent years, insects have been selected as a valuable tool for food waste treatment owing to their capability to transform low-value food waste into biomass with high nutritional value. Bakery wastes can be used profitably for this purpose. This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Various studies have reported the influence of adding natural ingredients on the functional properties of cakes (Luo et al 2020;Indriani et al 2020;Lenka, Kumari, and Pradhan 2020;Taglieri et al 2022). However, according to our knowledge, no study has been conducted about the fortification of sponge cake by green and white tea and ginger extracts.…”
Section: Physicochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the influence of adding natural ingredients on the functional properties of cakes (Luo et al 2020;Indriani et al 2020;Lenka, Kumari, and Pradhan 2020;Taglieri et al 2022). However, according to our knowledge, no study has been conducted about the fortification of sponge cake by green and white tea and ginger extracts.…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…The panelists reported that the size of the crumb porous was smaller in fortified samples with extracts, compared to the control sample. Studies reported a reduction trend in specific volume after addition of phenolic compounds during cake formulation because of disruption in gluten network and reduced gas-retention capacity (Mahmoudi et al 2020;Taglieri et al 2022;Usman et al 2020;Kırbaş, Kumcuoglu, and Tavman 2019;Lavelli and Corti 2011).…”
Section: Appearance Scorementioning
confidence: 99%
“…4 Edible insects have high protein and fat contents and are excellent food substitutes, especially for meat. [5][6][7] Compared to that of other proteins of animal origin, the production of insect proteins causes less environmental pollution and has higher economic value. 8,9 In a previous study, Osimani et al 10 reported a linear correlation between the protein, fat and fiber contents and the amount of cricket powder added to a meal.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification of sustainable alternative protein sources has attracted the attention of the scientific community 4 . Edible insects have high protein and fat contents and are excellent food substitutes, especially for meat 5‐7 . Compared to that of other proteins of animal origin, the production of insect proteins causes less environmental pollution and has higher economic value 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have documented the successful augmentation of various baking and confectionery products with natural ingredients and their impact on the functional properties of cakes [ 9 , [14] , [15] , [16] , [17] , [18] ]. To our knowledge, there is no publication that examines the cocoa and mint enrichment of sponge cakes, therefore the aim of the study was to make sponge cakes with the addition of Dutch cocoa powder and three different types of mint ( Mentha x piperita L., Mentha spicata var.…”
Section: Introductionmentioning
confidence: 99%